Th1 Differentiation Drives the Accumulation of Intravascular, Non-protective CD4 T Cells during Tuberculosis - Michelle A. Sallin; Shunsuke Sakai; Keith D. Kauffman; Howard A. Young; Jinfang Zhu; Daniel L. Barber (Cell Reports, 2017)
Recent data indicate that the differentiation state of Th1 cells determines their protective capacity against tuberculosis. Therefore, we examined the role of Th1-polarizing factors in the generation of protective and non-protective subsets of Mtb-specific Th1 cells. We find that IL-12/23p40 promotes Th1 cell expansion and maturation beyond the CD73+CXCR3+T-betdim stage, and T-bet prevents deviation of Th1 cells into Th17 cells. Nevertheless, IL- 12/23p40 and T-bet are also essential for the production of a prominent subset of intravascular CX3CR1+KLRG1+ Th1 cells that persists poorly and can neither migrate into the lung parenchyma nor control Mtb growth. Furthermore, T-bet suppresses development of CD69+CD103+ tissue resident phenotype effectors in lung. In contrast, Th1-cell-derived IFN-γ inhibits the accumulation of intravascular CX3CR1+KLRG1+ Th1 cells. Thus, although IL-12 and T-bet are essential host survival factors, they simultaneously oppose lung CD4 T cell responses at several levels, demonstrating the dual nature of Th1 polarization in tuberculosis.